Posterior Neocortex-Specific Regulation of Neuronal Migration by CEP85L Identifies Maternal Centriole-Dependent Activation of CDK5. - Kodani, Andrew; Kenny, Connor; Lai, Abbe; Gonzalez, Dilenny M; Stronge, Edward; Sejourne, Gabrielle M; Isacco, Laura; Partlow, Jennifer N; O'Donnell, Anne; McWalter, Kirsty; Byrne, Alicia B; Barkovich, A James; et al. (Neuron, 2020)
Genes mutated in human neuronal migration disorders encode tubulin proteins and a variety of tubulin-binding and -regulating proteins, but it is very poorly understood how these proteins function together to coordinate migration. Additionally, the way in which regional differences in neocortical migration are controlled is completely unknown. Here we describe a new syndrome with remarkably region-specific effects on neuronal migration in the posterior cortex, reflecting de novo variants in CEP85L. We show that CEP85L is required cell autonomously in vivo and in vitro for migration, that it localizes to the maternal centriole, and that it forms a complex with many other proteins required for migration, including CDK5, LIS1, NDE1, KIF2A, and DYNC1H1. Loss of CEP85L disrupts CDK5 localization and activation, leading to centrosome disorganization and disrupted microtubule cytoskeleton organization. Together, our findings suggest that CEP85L highlights a complex that controls CDK5 activity to promote neuronal migration.
Keywords: Cell Movement; Centrioles; Child; Child, Preschool; Cyclin-Dependent Kinase 5; Cytoskeletal Proteins; Female; Humans; Lissencephaly; Male; Microtubules; Neocortex; Nerve Tissue Proteins; Neurons; Oncogene Proteins, Fusion; Young Adult

PRUNE is crucial for normal brain development and mutated in microcephaly with neurodevelopmental impairment. - Zollo, Massimo; Ahmed, Mustafa; Ferrucci, Veronica; Salpietro, Vincenzo; Asadzadeh, Fatemeh; Carotenuto, Marianeve; Maroofian, Reza; Al-Amri, Ahmed; Singh, Royana; Scognamiglio, Iolanda; Mojarrad, Majid; Musella, Luca; et al. (Brain, 2017)
PRUNE is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily of molecules important for cell motility, and implicated in cancer progression. Here we investigated multiple families from Oman, India, Iran and Italy with individuals affected by a new autosomal recessive neurodevelopmental and degenerative disorder in which the cardinal features include primary microcephaly and profound global developmental delay. Our genetic studies identified biallelic mutations of PRUNE1 as responsible. Our functional assays of disease-associated variant alleles revealed impaired microtubule polymerization, as well as cell migration and proliferation properties, of mutant PRUNE. Additionally, our studies also highlight a potential new role for PRUNE during microtubule polymerization, which is essential for the cytoskeletal rearrangements that occur during cellular division and proliferation. Together these studies define PRUNE as a molecule fundamental for normal human cortical development and define cellular and clinical consequences associated with PRUNE mutation.
Keywords: Adolescent; Brain; Carrier Proteins; Cell Differentiation; Cell Movement; Cerebral Cortex; Child; Child, Preschool; Cytoskeleton; Developmental Disabilities; Female; Genes, Recessive; Heredodegenerative Disorders, Nervous System; Humans; Infant; Male; Microcephaly; Microtubules; Mutation; Pedigree; Young Adult

Mutations in Either TUBB or MAPRE2 Cause Circumferential Skin Creases Kunze Type. - Isrie, Mala; Breuss, Martin; Tian, Guoling; Hansen, Andi Harley; Cristofoli, Francesca; Morandell, Jasmin; Kupchinsky, Zachari A; Sifrim, Alejandro; Rodriguez-Rodriguez, Celia Maria; Dapena, Elena Porta; Doonanco, Kurston; Leonard, Norma; et al. (Am J Hum Genet, 2015)
Circumferential skin creases Kunze type (CSC-KT) is a specific congenital entity with an unknown genetic cause. The disease phenotype comprises characteristic circumferential skin creases accompanied by intellectual disability, a cleft palate, short stature, and dysmorphic features. Here, we report that mutations in either MAPRE2 or TUBB underlie the genetic origin of this syndrome. MAPRE2 encodes a member of the microtubule end-binding family of proteins that bind to the guanosine triphosphate cap at growing microtubule plus ends, and TUBB encodes a β-tubulin isotype that is expressed abundantly in the developing brain. Functional analyses of the TUBB mutants show multiple defects in the chaperone-dependent tubulin heterodimer folding and assembly pathway that leads to a compromised yield of native heterodimers. The TUBB mutations also have an impact on microtubule dynamics. For MAPRE2, we show that the mutations result in enhanced MAPRE2 binding to microtubules, implying an increased dwell time at microtubule plus ends. Further, in vivo analysis of MAPRE2 mutations in a zebrafish model of craniofacial development shows that the variants most likely perturb the patterning of branchial arches, either through excessive activity (under a recessive paradigm) or through haploinsufficiency (dominant de novo paradigm). Taken together, our data add CSC-KT to the growing list of tubulinopathies and highlight how multiple inheritance paradigms can affect dosage-sensitive biological systems so as to result in the same clinical defect.
Keywords: Adolescent; Animals; Brain; Child; Cutis Laxa; Female; Gene Dosage; Gene Expression Regulation, Developmental; Genes, Recessive; Hamartoma; Haploinsufficiency; Humans; Infant; Inheritance Patterns; Male; Microtubule-Associated Proteins; Microtubules; Mutation; Protein Folding; Protein Multimerization; Skin; Skin Abnormalities; Tubulin; Young Adult; Zebrafish